A new inner-city specialist programme reduces readmission rates in frequently admitted patients with bipolar disorder. (28th November 2018) - Macritchie, Karine; Mantingh, Tim; Hidalgo-Mazzei, Diego; Bourne, Sarah; Borthwick, Emma; Young, Allan H.
Abstract : Aims and method: The OPTIMA mood disorders service is a newly established specialist programme for people with bipolar disorder requiring frequent admissions. This audit compared data on hospital admissions and home treatment team (HTT) spells in patients before entry to and after discharge from the core programme. We included patients admitted between April 2015 and March 2017 who were subsequently discharged. Basic demographic data and numbers of admissions and HTT spells three years before and after discharge were collected and analysed. Results: Thirty patients who completed the programme were included in the analyses. The median monthly rate of hospital admissions after OPTIMA was significantly reduced compared with the rate prior to the programme. HTT utilisation was numerically reduced, but this difference was not statistically significant. Clinical implications: These results highlight the effectiveness and importance of individually tailored, specialist care for patients with bipolar disorder following discharge from hospital. Declaration of interest: None.